Surface waves with negative phase velocity supported by temperature-dependent hyperbolic materials. (10th July 2019) - Mackay, Tom G; Lakhtakia, Akhlesh
Abstract: A numerical investigation was undertaken to elucidate the propagation of electromagnetic surface waves guided by the planar interface of two temperature-sensitive materials. One partnering material was chosen to be isotropic and the other to be anisotropic. Both partnering materials were engineered composite materials, based on the temperature-sensitive semiconductor InSb. At low temperatures the anisotropic partnering material is a non-hyperbolic uniaxial material; as the temperature is raised this material becomes a hyperbolic uniaxial material. At low temperatures, a solitary Dyakonov wave propagates along any specific direction in a range of directions parallel to the planar interface. At high temperatures, up to three different surface waves can propagate in certain directions parallel to the planar interface; one of these surface waves propagates with negative phase velocity (NPV). At a fixed temperature, the range of directions for NPV propagation decreases uniformly in extent as the volume fraction of InSb in the isotropic partnering material decreases. At a fixed volume fraction of InSb in the isotropic partnering material, the angular range for NPV propagation varies substantially as the temperature varies.